Behavioural and Ecological Consequences of Urban Life in Birds - Caroline Isaksson (Frontiers Research Topics, 2018)
Urbanization is next to global warming the largest threat to biodiversity. Indeed, it is becoming increasingly evident that many bird species get locally extinct as a result of urban development. However, many bird species benefit from urbanization, especially through the abundance of human-provided resources, and increase in abundance and densities. These birds are intriguing to study in relation to its resilience and adaption to urban environments, but also in relation to its susceptibility and the potential costs of urban life. This Research Topic consisting of 30 articles (one review, two meta-analyzes and 27 original data papers) provides insights into species and population responses to urbanization through diverse lenses, including biogeography, community ecology, behaviour, life history evolution, and physiology.